Digital Infrastructure and Leadership in Driving School Performance and Graduate Quality: Evidence from Indonesia - Maisyaroh, Maisyaroh; Ulfatin, Nurul; Mustiningsih, Mustiningsih; Adha, Maulana Amirul; Valdez, Anabelie Villa; Ariyanti, Nova Syafira (International Review of Management and Marketing, 2026)
This study examines the influence of digital infrastructure readiness and digital leadership on the implementation of school administration, academic outcomes, and the quality of madrasah graduates in Indonesia. This research utilised a quantitative approach and structural equation modelling (SEM) to conduct a survey of principals and teachers in various madrasahs throughout East Java Province. The results demonstrated that readiness in digital infrastructure and robust digital leadership significantly improved the effectiveness of SBM, thereby positively impacting school performance and the quality of graduates. This study emphasises the significance of investing in technology and cultivating digital leadership in madrasahs to enhance educational quality. The results underscore the necessity of collaboration among educational institutions, communities, and governmental bodies to advance the establishment of sustainable digital infrastructure. This study enhances the current literature by offering empirical data about the essential role of digital infrastructure and leadership in Islamic education in Indonesia.